The Effects of Simulation-Based Advanced Life Support Education for Nursing Students. Issue 5 (May 2020) - Kim, Sung Hwan; Issenberg, Barry; Roh, Young Sook
Abstract : Advanced life support education for nursing students is very important because nurses are first responders in emergency situations. The purpose of this study was to identify the effects of simulation-based advanced life support education on nursing students' knowledge, performance, self-efficacy, and teamwork. A nonequivalent control group posttest-only design was used. Fourth-year nursing students were randomly assigned to either simulation-based Korean Advanced Life Support (n = 30) or lecture-based education (n = 30) groups. Data were analyzed using descriptive statistics and the Mann-Whitney U test. The experimental group showed statistically significant higher scores in knowledge ( P < .001), performance ( P < .001), and self-efficacy ( P = .049) when compared with the control group. However, there was no significant difference in teamwork scores between the two groups ( P = .529). The 4.5-hour simulation-based Korean Advanced Life Support education was more effective than the 4.5-hour lecture-based education for nursing students in terms of knowledge, performance, and self-efficacy. Nurse educators should adopt simulation-based advanced life support education into the curriculum for the optimal competence of nursing students.